2020
DOI: 10.3390/cells9041016
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of X Chromosome Inactivation during Bovine Embryo Development

Abstract: X-chromosome inactivation (XCI) is a developmental process that aims to equalize the dosage of X-linked gene products between XY males and XX females in eutherian mammals. In female mouse embryos, paternal XCI is initiated at the 4-cell stage; however, the X chromosome is reactivated in the inner cell mass cells of blastocysts, and random XCI is subsequently initiated in epiblast cells. However, recent findings show that the patterns of XCI are not conserved among mammals. In this study, we used quantitative R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 57 publications
2
28
0
1
Order By: Relevance
“…Finally, we performed a gene specific bisulfite sequencing in order to analyze whether DMR methylation patterns were related to the high expression of XIST and KCNQ1OT1. As for the XIST DMR, all groups were demethylated, which is in accordance with its biallelic expression at during the early stages of bovine embryogenesis (Bermejo-Alvarez et al, 2010; Yu et al, 2020). In bovine sperm cells, the XIST gene does not appear methylated (Mendonca et al, 2019), suggesting that XIST would be expressed in androgenetic cells It is likely that the XIST DMR undergoes methylation later during embryonic development, as the onset of XCI initiates at blastocyst stage (Yu et al, 2020).…”
Section: Discusionsupporting
confidence: 65%
See 2 more Smart Citations
“…Finally, we performed a gene specific bisulfite sequencing in order to analyze whether DMR methylation patterns were related to the high expression of XIST and KCNQ1OT1. As for the XIST DMR, all groups were demethylated, which is in accordance with its biallelic expression at during the early stages of bovine embryogenesis (Bermejo-Alvarez et al, 2010; Yu et al, 2020). In bovine sperm cells, the XIST gene does not appear methylated (Mendonca et al, 2019), suggesting that XIST would be expressed in androgenetic cells It is likely that the XIST DMR undergoes methylation later during embryonic development, as the onset of XCI initiates at blastocyst stage (Yu et al, 2020).…”
Section: Discusionsupporting
confidence: 65%
“…A recent report has indicated that XIST accumulation and XCI in bovine embryos starts at the morula stage. However, XIST colocalization with repressive marks (H3 lysine 27 trimethylation) on histones was only detected by day 7 blastocysts, indicating that complete XCI is only partially achieved at the blastocyst stage (Yu et al, 2020). Although XIST accumulation did not lead to globally reduced expression of X-linked genes, and X-Chr inactivation is only partially achieved at the blastocyst stage (Bermejo-Alvarez et al, 2010; Yu et al, 2020), the effects of the dysregulated expression of this long-noncoding RNA in haploid androgenetic morulas and blastocyst stages needs further investigation to clarify its impacts on chromosome-wide downregulation of gene expression.…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the blastocyst stage, human as well as rabbit express XIST (the RNA that initiates the silencing cascade) from both alleles, while mouse has exclusively paternal Xist expression [ 1 ]. Cow has been observed to upregulate XIST at a similar stage to human and rabbit [ 12 ]. Human and rabbit also showed later inactivation timing than mouse [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the blastocyst stage, human as well as rabbit express XIST (the RNA that initiates the silencing cascade) from both alleles, while mouse has exclusively paternal Xist expression [1]. Cow has been observed to upregulate XIST at a similar stage to human and rabbit [12]. Human and rabbit also showed later inactivation timing than mouse [1].…”
Section: Introductionmentioning
confidence: 99%